Becoming and development of scientific knowledge about local self-government: theoretical and legalaspect - Русанова, Світлана Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article is sanctified to research of becoming the scientific knowledge about local self-government in Ukraine. The world famous conceptions of local self-government and display of these conceptions in a home legislation are analysed.